A Project Report on Finite Element Modeling Of Thermosonic Wave Based Detection of Crack In Mtal Plate - SHASHISHEKARAYYA R HIREMATH (2011)
INTERNAL GUIDE : Srinivasan EXTERNAL GUIDE: D Roy Mahapatra USN NO : 1MJ09MAE12 CARRIED OUT AT : National Aerospace Laboratories Bangalore-560017 ACC NO : AE22
Keywords: Modeling Of Thermosonic